Impact of a multidisciplinary team training programme on rectal cancer outcomes in Spain. (25th April 2013) - Ortiz, H.; Wibe, A.; Ciga, M. A.; Lujan, J.; Codina, A.; Biondo, S.; ,
Abstract Aim The Spanish Rectal Cancer Project was established in 2006, inspired by the Norwegian Rectal Cancer Project. It consisted of an educational project aiming to introduce mesorectal excision surgery to surgeons, pathologists and radiologists. Its effect on local recurrence (LR) was compared with the Norwegian Project. Method An observational cohort study was carried out including all patients (4700) with rectal cancer from a population of 19 329 992 inhabitants operated on in 51 Spanish hospitals between March 2006 and June 2010. Curative resection was defined as a resection with an uninvolved circumferential margin in patients without distant metastases and without intra‐operative rectal perforation. The effectiveness of the programme was measured by a central registry with feedback to participating institutions of their own results compared with the national average. The main outcome measures were LR and adverse effects in curative resections. Results Of the 4700 patients, 3213 had a resection considered to be curative. LR rates were 4.7% (95% CI 0.03–0.59), metastasis rate was 16% (95% CI 0.14–0.17) and overall survival was 87.8% (95% CI 0.86–0.89). Multivariate analysis showed that advanced TNM stage and decreasing distance of the tumour from the anal verge had a negative influence on LR. Conclusion This study shows that the results obtained in Norway have been reproduced in a larger population in Spain applying a similar methodology.